2016
DOI: 10.1515/applirev-2016-0020
|View full text |Cite
|
Sign up to set email alerts
|

“Where are you really from?”: Nationality and Ethnicity Talk (NET) in everyday interactions

Abstract: The article examines the significance of questions such as "where are you really from?" in everyday conversational interactions. Defining this kind of talk as nationality and ethnicity talk (NET), i. e. discourse that either explicitly or inexplicitly evokes one's nationality or ethnicity in everyday conversation, the paper discusses what constitutes NET, how it works through symbolic and indexical cues and strategic emphasis, and why it matters in the wider context of identity, race, intercultural contact and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…The study's findings revealed that participants are constantly torn between these two poles or societal forces, having to negotiate between their (linguistic) identity, the expression of their own voice, and a sense of belonging on the one hand and emancipation, participation, and socioeconomic opportunities on the other. Put differently, they are caught in a positionality struggle between tradition and globalization (Hua & Li, 2016). Great tensions exist regarding Swiss German, its questioned legitimate status due to language policies and laws prioritizing SSG, and its discriminatory nature vis-à-vis other (national) language groups, given Switzerland's diglossic situation.…”
Section: Symbolic Power and Legitimacy In The 'Native-speaker' And 'S...mentioning
confidence: 99%
See 1 more Smart Citation
“…The study's findings revealed that participants are constantly torn between these two poles or societal forces, having to negotiate between their (linguistic) identity, the expression of their own voice, and a sense of belonging on the one hand and emancipation, participation, and socioeconomic opportunities on the other. Put differently, they are caught in a positionality struggle between tradition and globalization (Hua & Li, 2016). Great tensions exist regarding Swiss German, its questioned legitimate status due to language policies and laws prioritizing SSG, and its discriminatory nature vis-à-vis other (national) language groups, given Switzerland's diglossic situation.…”
Section: Symbolic Power and Legitimacy In The 'Native-speaker' And 'S...mentioning
confidence: 99%
“…Adya's problematical lived experiences of language, for instance, incorporate the phenomenon of (perceived) necessity of passing that is embedded in what Hua and Li (2016) have coined 'nationality and ethnicity talk.' According to them, this kind of discourse "is essentially an act of identity calibration and involves categorization and positioning of self and others and stance-making" (Hua & Li, 2016, p. 450) in an effort to answer the question 'Where are you really from?'…”
Section: Symbolic Power and Legitimacy In The 'Native-speaker' And 'S...mentioning
confidence: 99%
“…In contemporary diasporic contexts, community relations and membership are seen as complex and continuously reconstructed and boundaries between communities as malleable and permeable (Wei, 2018). Studies on language and identity have highlighted that language practices may not neatly map onto national, ethnic or cultural affiliations (Hua and Wei, 2016), that there may be a mismatch between language proficiency in the heritage language and a sense of cultural belonging (Canagarajah, 2008) and that group membership is dynamic and affiliation and inheritance are negotiated (Rampton, 1995). At the same time, it is important to remember that fluid and flexible conceptualisations of language, identity and diaspora community "may be at odds with widely-held beliefs among participants who often see 'their' language, identity and community as bounded objects that have remained unchanged over time and across space.…”
Section: An Emergent and Discursively Constructed View Of Identitiesmentioning
confidence: 99%
“…Much less is known about how children acquire knowledge of less common, but still culturally meaningful, registers with which they lack first-hand experience as an addressee. For native learners of English growing up in a largely monolingual environment, one such example is Foreigner Talk, a means of speaking that native speakers tend to adopt when addressing non-native speakers (Biersack, Kempe, & Knapton, 2005; Chun, 2009; Ferguson, 1975; Gass, 1997; Gass & Varonis, 1985; Hua & Wei, 2016; Long, 1981; Ravid, Olshtain, & Ze’elon, 2003; Uther et al, 2007). Foreigner Talk typically consists of shorter utterances, the omission of inflectional morphology and other words, and more uninverted interrogative sentence structures, although it does not entail a distinct grammar (Ferguson, 1975; Freed, 1981; Long, 1981, 1983a, 1983b; Roche, 1998).…”
mentioning
confidence: 99%